Resident evil. The final chapter [videorecording (DVD)] - Jovovich, Milla; Glen, Iain, 1961-; Larter, Ali, 1976-; Roberts, Shawn, 1984-; Rose, Ruby, 1986-; Macken, Eoin C.; James, Fraser; Levy, William, 1980- (Sony Pictures Home Entertainment, 2017)
Picking up immediately after the events in Resident Evil: Retribution, Alice is the only survivor of what was meant to be humanity's final stand against the undead. Now, she must return to where the nightmare began, The Hive in Raccoon City, where the Umbrella Corporation is gathering its forces for a final strike against the only remaining survivors of the apocalypse.